2011
DOI: 10.1071/cp10406
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution profiles and temporal growth patterns of roots in selected oilseeds, pulses and spring wheat

Abstract: Knowledge of rooting systems and their vertical distribution in the soil profile for field crops is required for designing crop rotation systems that allow for effective use of soil water and nutrients. This study determined the vertical distribution in the upper 100 cm of the soil profile and the temporal growth patterns of roots for three pulses (Cicer arietinum L. chickpea, Pisum sativum L. dry pea, and Lens culinaris Medik. lentil) and three oilseeds (napus canola, juncea mustard, and Linum usitatissimum f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…We did not measure the distribution of maize roots belowground in the present study, but other researchers have indicated that cereals can spread their roots underneath a legume crop and root deeply and extensively in the soil profile (Adiku et al, 2001). Pea plants have a shallow rooting depth under semiarid environments (Gan et al, 2011), with a limited competitiveness for resources with cereal crops (Manschadi et al, 1998). Additionally, pea plants may provide some portion of the fixed‐N to the maize (Xiao et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…We did not measure the distribution of maize roots belowground in the present study, but other researchers have indicated that cereals can spread their roots underneath a legume crop and root deeply and extensively in the soil profile (Adiku et al, 2001). Pea plants have a shallow rooting depth under semiarid environments (Gan et al, 2011), with a limited competitiveness for resources with cereal crops (Manschadi et al, 1998). Additionally, pea plants may provide some portion of the fixed‐N to the maize (Xiao et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The great depths to which tree roots extend Jackson et al, 1996;Maeght et al, 2013;Freycon et al, 2014;Fan (Acuna and Wade, 2013;Ahmadi et al, 2011;Gan et al, 2011;Neykova et al, 2011;Trachsel et al, 2013), and the centennial timescale over which forest roots continue to expand (Zangaro et al, 2008;Knops and Bradley, 2009;Devine et al, 2011;Yuan & Chen, 2012;Sun et al, 2015) are widely observed phenomena. However, to our knowledge the current study is the first to quantify root densities to such depths in replicated plots representing distinct disturbance histories, and to determine a meaningful influence of forest age on rooting depth distributions.…”
Section: Well-developed Rooting Systems Pump Photosynthate Deep Into mentioning
confidence: 99%
“…However, it is not known whether diversifying summerfallow systems with pulses is effective and productive in the northern latitude areas where water is scarce and the growing season is short (95 to 125 days) 25 . Our proposal for diversifying summerfallow systems with short-season pulses is largely based on the latest research on pulses: (a) pulse plants in the northern latitudes have a shallow rooting depth 26 with approximately 77-85% of the roots being located in the 0-0.4 m soil depth 27 , which allows pulse crops to use water mainly from the top 0.6 m soil layer, leaving water in the deeper soil layers (below 0.6 cm) 28 for use by deeper-rooted crops that are grown the following year 29 ; (b) dry pea and lentil, the two main annual pulses grown in the semiarid northern Great Plains, use 15-35% less water than cereal or oilseed crops, thereby enhancing water use efficiency 30 ; (c) pulses are typically harvested several weeks earlier than cereal or oilseed crops, leaving a longer postharvest period during which soil water can accumulate prior to planting crops the following spring 31 ; (d) the inclusion of pulse crops in the rotation can increase crop yields, decrease inputs of inorganic N fertilizer 32 , and enhance N use efficiency 33 ; and finally (e) long-term studies have shown that crop diversification with pulses and oilseed can improve overall farming sustainability 6 . The central hypothesis of the present study is that diversifying cropping systems with pulse crops can improve the attributes of soil water conservation and soil N benefits and increase total grain production.…”
mentioning
confidence: 99%